(untitled) (Proceeding of the International Conference on Arts and Humanities, 2024)
In Vietnam today, dresses are a very popular type of clothing in Vietnamese life. Although the dress is not a traditional Vietnamese clothing, due to its simple structure and shape, the dress is loved and worn by Vietnamese women for many different purposes and situations such as walking on the street, going to work, taking part to parties or weddings... Currently, there are many ways to decorate dresses such as beading, appliqués, printing, dyeing, drawing, pleating,... And one of the ways to decorate dresses not only increases their value, is less out of fashion, but also associates with Vietnamese tradition is the hand embroidery technique. Creating decorative embroidery motifs on dresses not only contributes to enhancing the beauty of the outfit but also contributes to spread and promote the values of traditional Vietnamese embroidery art. Therefore, this study aims to understand the unique features of hand embroidery techniques shown on women’s dresses today in Ho Chi Minh City, specifically via designs, colors, materials, patterns, motifs, layouts, and methods to implementive. The research used the method of researching specialized documents related to hand embroidery techniques, materials for sewing embroidered dresses, and the survey method about embroidered dress designs today in Ho Chi Minh City. The result of the research is a statistical table about the art of decorative embroidery on dresses in Ho Chi Minh City via characteristics such as style, color, material, motif, layout, and implementation techniques. Therefore, I hope that the research outcome contribute to the direction of future embroidered dress designs, meeting the aesthetic needs of women in Ho Chi Minh City.